A framework for m-health service development and success evaluation. (April 2018) - Sadegh, S. Saeedeh; Khakshour Saadat, Parisa; Sepehri, Mohammad Mehdi; Assadi, Vahid
Highlights: We have done a comprehensive literature review on famous frameworks and models in the field of Information Technology and e-health. An m-health evaluation framework has been proposed which evaluates the success of a given m-health service through a three-stage life cycle. The proposed framework consists of important measures from the viewpoint of key stakeholders. The proposed framework can be tailored to special m-Heath services such as physician-centered services and patient-centered services. Abstract: The emergence of mobile technology has influenced many service industries including health care. Mobile health (m-Health) applications have been used widely, and many services have been developed that have changed delivery systems and have improved effectiveness of health care services. Stakeholders of m-Health services have various resources and rights that lends to a complexity in service delivery. In addition, abundance of different m-Health services makes it difficult to choose an appropriate service for these stakeholders that include customers, patients, users or even providers. Moreover, a comprehensive framework is not yet provided in the literature that would help manage and evaluate m-health services, considering various stakeholder's benefits. In this paper, a comprehensive literature review has been done on famous frameworks and models in the field of Information Technology and electronic health with the aim of finding different aspects of developing and managing m-health services. Using the results of literature review and conducting a stakeholder analysis, we have proposed an m-health evaluation framework which evaluates the success of a given m-health service through a three-stage life cycle: (1) Service Requirement Analysis, (2) Service Development, and (3) Service Delivery. Key factors of m-health evaluation in each step are introduced in the proposed framework considering m-health key stakeholder's benefits. The proposed framework is validated via expert interviews, and key factors in each evaluation step is validated using PLS model. Results show that path coefficients are higher than their threshold which supports the validity of proposed framework.